Study on Risk factors, presentation and management of stroke in a tertiary care hospital - Sapkota, S; Chhetri, H; Sharma, RP (Janaki Medical College Journal of Medical Science, 2014)
Background and Objectives: Many studies in recent years have focused attention on identification of risk factors associated with stroke. However, most of these studies have been conducted in the developed countries. Only few studies have been conducted in Nepal. So the present study has been undertaken with the aim of determining the risk factors and management pattern of stroke and makes the people aware of those factors. Material and Methods: It is a descriptive prospective study conducted with 50 consecutive patients who presented in medicine and emergency department at Universal College of Medical Science, Bhairahawa, Nepal from December 2009 to July 2010. Data were collected using a standard questionnaire and encounter form after receiving a verbal consent from the patient. The collected data were coded, tabulated and analyzed using SPSS version- 16. Results: The present study showed that 56% of stroke patients were male. Hemorrhagic stroke (60%) was more than the ischemic stroke (40%).The age was common non modifiable risk factor. The common–modifiable risk factors were hypertension (86%), alcohol consumption (74%) and smoking (56%). Calcium channel blocker (44.18%) and combination of it with Diuretic (18.60%) and ACE inhibitors (20.93%) were the commonly prescribed drugs for lowering blood pressure. Prescribed drugs therapy and lifestyle modification improved the health condition of patients (80%). The non compliance to the drugs was due to multiple dosages (51.52%), side effects (18.18%) and forgetfulness (18.18%). Conclusion: Finding of this study will be helpful for the practitioners as well as researcher in the future. Practitioners can make people aware on the risk factors and preventive measures of the stroke. Researchers will be helped by knowing the commonest risk factors of stroke and its management pattern. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11394 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 35-43